Light sources and photodetectors enabled by 2D semiconductors - Shang, Jingzhi (2020)
The emerging 2D semiconductors have aroused increasing attention due to their fascinating fundamental properties and application prospects. Technical investigation of 2D semiconductor–based electronics and optoelectronics is paving the way to realizing practical applications, which opens up new opportunities to reshape the current semiconductor industry. Particularly, 2D semiconductor–based optoelectronics can be extensively utilized in the promising semiconductor and information industries, such as solid‐state lighting, on‐chip optical interconnects, quantum computing, and communication. Here, the research progress regarding the fabrication and characterization of rapidly growing light‐emitting devices and photodetectors enabled by 2D semiconductors is reviewed. According to different emission mechanisms, 2D semiconductor–activated light sources are classified into four types: excitonic light‐emitting diodes (LEDs), quantum LEDs, valley LEDs, and lasers. Moreover, photodetecting devices based on atomically thin MoS2, other 2D semiconductors, and van der Waals heterostructures are discussed, where diverse device structures, performance parameters, and working principles are compared. Furthermore, the remaining challenges in the realization of practical devices with desirable features are outlined and new research opportunities for 2D semiconductor optoelectronics are proposed.